Analisis Penyelesaian Pada Permasalahan Pure Integer Linear Programming Dengan Menggunakan Metode Branch And Bound Dan Cutting Plane - Azhar Sinaga; Sawaluddin Sawaluddin (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
The use of the Branch and Bound method has few errors but requires more calculations. Meanwhile, the Cutting Plane method reaches the optimum faster because with the addition of the Gomory constraint it is effective in eliminating continuous solutions. Cutting Plane method is better to use if there are few variables, namely 2 variables. In this study, it is shown how a Pure Integer Linear Programming problem is solved using the branch and bound and cutting plane methods with the problem of variable coefficient constraints on fractions and integers with 4 variables. And it is found that the Branch and Bound method is better used in pure integer linear programming problems with variable coefficients of fractional number constraints. While the Cutting Plane method is better used on the coefficients of integer constraints variables